Pengaruh Penambahan Semen Portland (PC) Terhadap Karakteristik Marshall Pada Campuran Aspal Buton Tipe CPHMA - Rahman, Muh. Arif; Nurdin, Abd. Rahim; Cangara, Satriawati (Jurnal Penelitian Teknik Sipil Konsolidasi, 2025)
Asbuton is one of Indonesia's natural resources that can be utilized to improve road quality because it has an asphalt content of 10% to 35%. Cold Paving Hot Mix Asbuton (CPHMA) as a cold spread hot mix that occurs from aggregate, buton granules, rejuvenating agents and other added materials that have been mixed properly at the factory and marketed ready to be spread and compacted in asphalt road pavement. The aim of the study was to determine the effect of the addition of Portland cement on the characteristics of buton CPHMA asphalt mixture and to analyze the percentage of the best Portland cement content and meet the requirements for buton CPHMA asphalt mixture. This study used Portland cement with the addition of 4%, 8%, 12%, 16% and 20%. Testing is done with the marshall test tool. The results showed that with increasing levels of variation in Portland Cement, the stability, VFB, and MQ values decreased. The Flow, VMA, and VIM values have increased. The percentage of Portland cement content in the CPHMA Buton asphalt mixture is the best at a cement content of 12%.